(untitled) (Actualizaciones en Sida e Infectología, 2025)
Introduction: the “One Health” concept established by the World Health Organization, refers to the importance of a global approach to the human health, the animal health and that of the environment. The relationship and interconnection among them cannot be ignored when referring to the management of human being’s health. On the other side, the antimicrobial resistance is a bigger and growing world problem in every field, and it is the responsibility of each government to take prompt action to avoid this great issue continues. Objective: to investigate how the antimicrobials rests are disposed in the households in Concordia city so far in the year 2022. Methodology: the study used a quantitative approach through specific structured not self-administrated surveys, in a non-probabilistic sample of the population in the city of Concordia. For the analysis of the collected data, descriptive statistics were applied, which allowed obtaining absolute and relative frequencies of each variable measured in the study. Results: we could obtain a great number of data, not only regarding the initials objectives but also in relation to the understanding of the population according to the antimicrobials and the way to use them. Conclusions: overall, there are several shortcomings regarding the general knowledge of the population about the adequate use of the antibiotics, the understanding of the risks with the unnecessary use; and the way they must dispose them.